Component composition of communication competency and its measurement - Tkachov, Ivan V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
This paper defines communication competency in the framework of psychology. The relationship of communication competency with capacities and personal traits is analysed, and also its place in the system of psychological characteristics influencing communicative behaviour is clarified. The component composition of communication competency in the set of cognitive, emotional, behavioural and motivational components is characterised. Phenomena of social, emotional intelligence, the affiliation motive are considered in the structure of communication competency. The methods for measuring the above components of competency are presented.
Keywords: communication competency; social intelligence; emotional intelligence; affiliation motive; competency; communication; components of communication competency